2013
DOI: 10.1158/0008-5472.sabcs13-p6-10-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-10-03: Comparative efficacy of everolimus in combination with exemestane and chemotherapy for advanced breast cancer in terms of progression-free survival

Abstract: Background: For hormone receptor-positive (HR+) advanced breast cancer (ABC), guidelines recommend endocrine therapy as the preferred option even in the presence of visceral disease. If there is evidence of endocrine resistance or rapidly progressive disease requiring a fast response then chemotherapy is recommended. The randomized controlled trial (RCT) BOLERO-2 demonstrated that everolimus plus exemestane (EVE+EXE) more than doubled median progression-free survival (PFS) compared with placebo+EXE while still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The present comparative effectiveness findings are consistent with recent studies showing that HR+/HER2− mBC patients treated with everolimus-based therapy tended to have better OS [ 17 , 18 ] and PFS [ 19 ] than those treated with chemotherapy. For example, using a small sample of HR+/HER2− mBC patients, Pouget et al showed that everolimus plus endocrine therapy resulted in significantly longer OS than chemotherapy for patients pretreated with two or fewer lines of therapies for mBC [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present comparative effectiveness findings are consistent with recent studies showing that HR+/HER2− mBC patients treated with everolimus-based therapy tended to have better OS [ 17 , 18 ] and PFS [ 19 ] than those treated with chemotherapy. For example, using a small sample of HR+/HER2− mBC patients, Pouget et al showed that everolimus plus endocrine therapy resulted in significantly longer OS than chemotherapy for patients pretreated with two or fewer lines of therapies for mBC [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…For example, using a small sample of HR+/HER2− mBC patients, Pouget et al showed that everolimus plus endocrine therapy resulted in significantly longer OS than chemotherapy for patients pretreated with two or fewer lines of therapies for mBC [ 17 , 18 ]. Cope et al (2013) conducted a network meta-analysis of available mBC clinical trials and concluded that despite differences in patient characteristics across studies, everolimus/exemestane combinational therapy was associated with the longer mean PFS until 20 months compared to commonly-used chemotherapies such as capecitabine, doxorubicin, paclitaxel, and vinorelbine [ 19 ]. Future head-to-head clinical trial evidence will help further assess the comparative efficacy of everolimus-based therapy compared to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation